Characterization of three different sensory fibers by use of neonatal capsaicin treatment, spinal antagonism and a novel electrical stimulation-induced paw flexion test - Yamaguchi Asuka; Hald Andreas; Inoue Makoto; Matsumoto Misaki; Ueda Hiroshi (SAGE Publishing, 2006)
Abstract In the present study, we first report an in vivo characterization of flexor responses induced by three distinct sine-wave stimuli in the electrical stimulation-induced paw flexion (EPF) test in mice. The fixed sine-wave electric stimulations of 5 Hz (C-fiber), 250 Hz (Aδ-fiber) and 2000 Hz (Aβ-fiber) to the hind paw of mice induced a paw-flexion response and vocalization. The average threshold for paw flexor responses by sine-wave stimulations was much lower than that for vocalization. Neonatally (P3) pretreatment with capsaicin to degenerate polymodal substance P-ergic C-fiber neurons increased the threshold to 5 Hz (C-fiber) stimuli, but not to 250 Hz (Aδ-fiber) and 2000 Hz (Aβ-fiber). The flexor responses to 5 Hz stimuli were significantly blocked by intrathecal (i.t.) pretreatment with both CP-99994 and MK-801, an NK1 and NMDA receptor antagonist, respectively, but not by CNQX, an AMPA/kainate receptor antagonist. On the other hand, the flexor responses induced by 250 Hz stimuli were blocked by MK-801 (i.t.) but not by CP-99994 or CNQX. In contrast, flexor responses induced by 2000 Hz stimuli were only blocked by CNQX treatment. These data suggest that we have identified three pharmacologically different categories of responses mediated through different primary afferent fibers. Furthermore, we also carried out characterization of the in vivo functional sensitivity of each of the sensory fiber types in nerve-injured mice using the EPF test, and found that the threshold to both 250 Hz and 2000 Hz stimulations were markedly decreased, whereas the threshold to 5 Hz stimulations was significantly increased. Thus we found opposing effects on specific sensory fiber-mediated responses as a result of nerve injury in mice. These results also suggest that the EPF analysis is useful for the evaluation of plasticity in sensory functions in animal disease models.